PENANGANAN KEKERASAN TERHADAP PEREMPUAN DAN ANAK DI PROVINSI KALIMANTAN TIMUR - Dini Zulfiani; . Indrawati; Oktavianus Kondorura; Meuthia Sahda AF (Jurnal Administrative Reform, 2019)
The cases of violence against women and children in East Kalimantan from year to year are increasing. efforts to protect victims of violence have been carried out through prevention and handling. If violence has occurred, appropriate handling must be carried out so that victims can feel safe and protected. The research aims to find out and analyze way of handling the victims of violence, especially women and children in East Kalimantan Province. The type of research used in this study includes descriptive qualitative. The research location chosen was East Kalimantan Province. Data collection techniques in this study are Library Research and Field Work Research. The results found that the handling of victims of violence was carried out in accordance with the Minimum Service Standards set by the government from the service of complaints to repatriation and empowerment in accordance with the results of assessments from officers, besides referral / coordination with related parties in accordance with the conditions of the victims.Keyword: handling violence, women, children